Nodular Regenerative Hyperplasia (NRH): A Clinicopathologic and Immunohistochemical Study. (21st September 2018) - Mannan, Rifat; Anders, Robert; Oshima, Kiyoko
Abstract: Objectives: To illustrate the clinicopathologic features of NRH and evaluate the utility of immunohistochemistry (IHC) in diagnosis. Methods: All cases of NRH (2001–2017) were searched from a database and 28 cases were identified. Six cases without NRH were used as controls. Demographic details and clinical features were recorded. IHC was performed in 25 cases for CD34 (to detect sinusoidal capillarization) and glutamine synthetase (GS, for aberrant expression in noncentrizonal hepatocytes). Staining intensity was semiquantitatively evaluated (0–3). Individual grades for each stain were added to form an IHC score. Student paired t test was used for statistical analysis. Results: Average age was 47 years (range, 2–75; M = 15, F = 13). Etiological associations included rheumatologic diseases (n = 3; 9.4%); hematolymphoid neoplasms (n = 4; 12.5%); liver disease (vascular disease and transplant) (n = 2; 6.4%); renal disease, including transplant (n = 3; 9.4%); immunodeficiency state (n = 4; 2 HIV and 2 CVID; 12.5%); drugs (chemotherapy) (n = 2; 6.4%); idiopathic (n = 10; 31.3%); and unknown (n = 4; 12.5%). Two of the idiopathic cases were associated with mutation in the telomerase gene. Average IHC score (sum of CD34 and GS) was 4.3 (vs 2.0 for controls; P = .0002). IHC for CD34 showed 0 (n = 1, 4%), 1+ (n = 6, 24%), 2+ (n = 6, 24%), and 3+ (n = 12, 48%). IHC for GS showed 1+ (n = 4, 16%), 2+ (n = 13, 52%), and 3+ (n = 8, 32%). Average score was 2.16 for CD34 (control 0.3) and 2.16 for GS (control 1.67). Staining for CD34 was found to be significantly more frequent in patients than in controls ( P = .0001). GS showed more positive staining in NRH cases than controls but was not statistically significant ( P = .1665). Conclusion: NRH can have diverse etiologic associations. CD34 and GS can be helpful diagnostic adjuncts. Association with telomerase gene mutation in two of our cases raises the possibility of telomere shortening as an underrecognized etiology for NRH.